Roles of microRNA-192 in diabetic nephropathy: the clinical applications and mechanisms of action - Wan, Xiaoqing; Liao, Jian; Lai, Hongting; Zhang, Shilong; Cui, Jianling; Chen, Chunyan (Frontiers in Endocrinology, 2023)
Diabetes nephropathy (DN) is one of the most common and intractable microvascular complications of diabetes worldwide, serving as the main cause of terminal renal disease. Due to the lack of early specific symptoms and diagnostic markers, DN severely threatens the sufferer’s life. MicroRNA-192 (miR-192) was early identified in human renal cortical tissue and stored and excreted in urine as microvesicles. MiR-192 was found to be involved in the development of DN. For the first time, the present review summarized all the current evidence on the topic of the roles of miR-192 in DN. Finally, 28 studies (ten clinical trials and eighteen experimental studies) were eligible for thoroughly reviewing. Most of the clinical trials (7/10, 70%) indicated miR-192 might be a protective factor for DN development and progression, while the majority of experimental studies (14/18, 78%) suggested miR-192 might be a pathogenic factor for DN. Mechanistically, miR-192 interacts with various direct targeted proteins (i.e., ZEB1, ZEB2, SIP1, GLP1R, and Egr1) and signaling cascades (i.e., SMAD/TGF-β and PTEN/PI3K/AKT), together contribute to the pathogenesis of DN through epithelial-to-mesenchymal transition (EMT), extracellular matrix deposition, and fibrosis formation. The current review highlights the dual role of miR-192 in the development of DN. Further investigations are still warranted to illustrate this inconsistent phenomenon, which may facilitate promoting the therapeutic applications of miR-192 in predicting and treating DN.